KAJIAN PENYEDIAAN BAHAN BAKU PADA INDUSTRI RUMAH ADAT MINAHASA DI DESA TOMBASIAN BAWAH - Ivan Elther Kawalo; Hengki D. Walangitan; Johny S. Tasirin (COCOS, 2021)
ABSTRACTHumans use forest products in the form of wood to make ends meet. With the increasingdemand for wood, the community continues to strive to obtain wood in the manufacture of Minahasatraditional houses which are an economic producer. This study aims to describe the type of wood, woodsources and wood needs. The results showed that, 1) The types of wood used in the manufacture ofMinahasa traditional houses in Tombasian Bawah Village were: cempaka wood, nantu wood, red wood /pulutan. But the most widely used type of chrysolite wood. 2) The source of wood is obtained from thesurrounding forest areas in Tombasian Bawah, Tareran, Lapi, Talaitad and Suluun which are privateproperty. And the wood purchased is also private property. 3) The use of wood in the manufacture ofMinahasa traditional houses, namely: staircase, steps, beam, bottom, floor frame, floor, pillar, wallboards, doors, windows, upper beam frame, upper frame. 4) The amount of wood raw material needed tobuild a Minahasa traditional house: 1 room (7-8 m3), 2 rooms (12-17 m3) and 3 rooms (16 m3). It alldepends on the number of rooms, size, model and order.Keywords: Minahasa Traditional House. Raw Materials of Minahasa Traditional Houses